Diabetes Mellitus and Health Services: Access Gap During the COVID-19 Pandemic - Pinta Pudiyanti Siregar; Shahrul Rahman; Yulia Afrina Nasution (Universitas Muhammadiyah Sumatera Utara, 2023)
Abstract: Diabetes Mellitus is a significant health problem worldwide and its prevalence is increasing yearly. This fact is coupled with the problem of the discovery of a new virus known as SARS-CoV-2 or COVID-19. Many questions have been asked, starting from how to treat patients with diabetes and their access to treatment. As a disease with a high risk of complications, integrated diabetes health care is still underdeveloped. For this reason, it is necessary to search to see what gaps exist in the use of telemedicine-based health services so that themes of these discrepancies can be identified. This study uses the method of searching and reviewing 24 kinds of literature. There were gaps in access and health care for racial and ethnic minorities, Obstacles faced in the diagnosis of Diabetes, Obstacles to patients in self-monitoring of blood sugar, Gaps in providing care due to COVID-19, Gaps in access to diabetes drugs, insulin, SGLT2 in Type 2 Diabetes patients, Gaps in access to care for type 2 diabetes patients with cardiovascular disease, use in access to diabetes care, and using telemedicine. It is necessary to develop a healthcare strategy for patients with Diabetes, including the team, then glycaemic and control targets, as well as patient preferences and priorities.